2017
DOI: 10.1016/j.energy.2017.08.031
|View full text |Cite
|
Sign up to set email alerts
|

CO2 injection-induced fracturing in naturally fractured shale rocks

Abstract: Niobrara shale cubes of 20 cm from Colorado were employed to investigate gas and supercritical CO 2 injection-induced fracturing in naturally fractured caprocks of deep aquifers/depleted reservoirs and fractured shale reservoirs. Under tri-axial stresses, gas or supercritical CO 2 was injected into the center of the cubes to induce fracturing. Real-time pressure and temperature, acoustic wave, pressure decay, fracture coloring, and gas fracturing were used to characterize the fracturing process and fracture mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(25 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…The result in Figure shows that the permeability of the rock sample increases with increasing injection pressure. When the SCCO 2 injection pressure increases and exceeds the breakdown pressure of the preexisting fractures, it causes the propagation and damage of the micro‐fractures . In addition, an increase in the temperature of the injected SCCO 2 results in its volume expansion and viscosity reduction, accompanied by a decrease in the fracture temperature .…”
Section: Comparative Experimentsmentioning
confidence: 99%
“…The result in Figure shows that the permeability of the rock sample increases with increasing injection pressure. When the SCCO 2 injection pressure increases and exceeds the breakdown pressure of the preexisting fractures, it causes the propagation and damage of the micro‐fractures . In addition, an increase in the temperature of the injected SCCO 2 results in its volume expansion and viscosity reduction, accompanied by a decrease in the fracture temperature .…”
Section: Comparative Experimentsmentioning
confidence: 99%
“…[204][205][206][207] Due to its low viscosity and lack of surface tension, SC-CO 2 used as a fracture stimulation fluid, has the potential to lower the formation breakdown pressure and create more irregular multiple fractures compared to liquid CO 2 or water. Wang, et al 208 used the Niobrara shale to conduct fracturing experiments with gaseous and SC-CO 2 , as well as slickwater with the same confining pressures and temperature. They found that gaseous and SC-CO 2 induced fracturing occurred at much lower pressures than slickwater fracturing, which were 6.6 MPa, 9.6 MPa and 11.0 MPa, respectively.…”
Section: Using Sc-co 2 As a Fracturing Fluidmentioning
confidence: 99%
“…CO 2 presplitting blasting of a coal and rock mass with empty holes is completed under the combined action of stress waves and explosive gases 30,31 . If the tangential tensile stress derived from radial displacement exceeds the tensile strength of the coal and rock mass, it will generate radial cracks in the coal and rock mass; then, the explosive gas is filled the initially formed radial crack, and the crack propagates under a gas‐driven mode 32,33 . The physical model of CO 2 blasting in the entire empty hole of the coal and rock mass is expressed by Equations .…”
Section: Theoreticalmentioning
confidence: 99%